2009
DOI: 10.1111/j.1749-6632.2009.04610.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Myogenic Differentiation of Human Bone Marrow–Derived Mesenchymal Stem Cells as a Potential Treatment for Urethral Sphincter Muscle Repair

Abstract: To explore a new treatment strategy for urinary incontinence, human bone marrow mesenchymal stem cells (MSC) of the first in vitro passage were exposed to 5-azacytidine (AZA) to induce myogenic differentiation, and cultured for a total of six passages. Expression of stem cell surface antigens and intracellular alpha-actin was examined by flow cytometry at the end of each passage and compared to that of native MSC (not exposed to AZA) cultured in parallel. To analyze differentiation into striated muscle, expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 31 publications
1
42
0
Order By: Relevance
“…Bone-marrow-derived cells are especially suited for this purpose because they can differentiate into striated or smooth muscle cells, both in vitro and in vivo. 31 Previously, we showed that bone-marrow-derived cells of wild-type mice, when implanted into freeze-injured urinary bladders of nude mice where most of the smooth muscle was lost, differentiate into smooth muscle cells. 36 Further, the bonemarrow-derived cells, when situated in areas of damage, produce cytokines and growth factors based on available signals in the surrounding tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bone-marrow-derived cells are especially suited for this purpose because they can differentiate into striated or smooth muscle cells, both in vitro and in vivo. 31 Previously, we showed that bone-marrow-derived cells of wild-type mice, when implanted into freeze-injured urinary bladders of nude mice where most of the smooth muscle was lost, differentiate into smooth muscle cells. 36 Further, the bonemarrow-derived cells, when situated in areas of damage, produce cytokines and growth factors based on available signals in the surrounding tissues.…”
Section: Discussionmentioning
confidence: 99%
“…3,30 Our strategy to accomplish the regeneration of functional urethral sphincters is the utilization of autologous bone-marrow-derived cells. These cells are capable of differentiating both in vitro and in vivo along multiple pathways that include striated and smooth muscle 31 as well as bone, cartilage, adipose, neural cells, tendon, and connective tissue. [32][33][34] Further, in the translation to clinical therapy, autologous cells are superior to allogenic cells because the autologous cells are not burdened with immunological rejection or ethics problems.…”
mentioning
confidence: 99%
“…Mesenchymal stem cells have many advantages in this setting; namely, easy isolation, high proliferative potential and efficient plasticity in vivo. They can be derived from adipose tissue, synovial membrane or bone marrow [22]. A number of workers used adipose-derived MSCs in-vitro for myogenic differentiation [23] and in experimental animal models [24].…”
Section: Discussionmentioning
confidence: 99%
“…These cells can be isolated from many different sources such as bone marrow, muscle, adipose tissue, liver tissue, amniotic fluid, placenta, umbilical cord and dental pulp [16]. Table 1 summarizes the main animal studies which have been conducted in the last years using adult stem cells [17,18,19,20,21,22,23,24,25,26]. …”
Section: Stem Cell Therapymentioning
confidence: 99%